SEED GERMINATION OF THE CORPSE GIANT FLOWER Amorphophallus titanum (Becc.) Becc. Ex Arcang: THE INFLUENCE OF TESTA [Perkecambahan Biji Bunga Bangkai Raksasa Amorphophallus titanum (Becc.) Becc. ex Arcang: Pengaruh Testa] - Latifah, Dian; Purwantoro, RS (BERITA BIOLOGI, 2015)
Amorphophallus titanum is famous as the gigantic inflorescense and economically prospective due to its 20% glucomannan contents.Various cultivation techniques including germination have been conducted due to the delay in the seed germination of Amorphophallus titanum. Previous studies revealed that A. titanum seeds has not produced faster and better germination rate.Therefore this research was aimed to test the following hypotheses: (1) Fruit pericarp and the pericarp inhibited the germination,(2) testa/seed coat inhibited germination, (3) GA3hormone promoted the germination rate.The germination pattern was also monitored. The experiments consisted of:Experiment 1: sowing the fruit with the seeds inside and Experiment 2 with two treatments: testa peeling and GA3 hormone treatments. The results of Experiment 1 showed that the fruit pericarp and the pericarp inhibited the germination for 124 days. Experiment 2 resulted in: (1) the delay of the germination for 7-35 days caused by the testa/seed coat, (2) GA3 hormone promoted the germination rate 2.19 coefficient of germination rate; and higher GA3 (1000 ppm) may enhance the seedling growth (reached the highest 23.6 ± 1.3).We also recorded developmental stages from the seed germination, first-leaf emergence and tuber development in series of photographs overtime during the experimental period.